Morpho-Physiology of Mulberry (Morus sp.) Plant on Salinity Stress Tolerance - Yasinta Ratna Esti Wulandari; Yohana Caecilia Sulistyaningsih; Agik Suprayogi; Min Rahminiwati; Triadiati Triadiati (Bogor Agricultural University, Indonesia, 2023)
The accession of mulberry (Morus sp.) with salinity tolerance unavailable in Indonesia is needed to overcome the problem of marginal land, especially in the saline areas of the country. Therefore, this research aims to determine the accession of salinity tolerance of mulberry from 6 origins in Indonesia based on growth and physiological parameters. The method used was a factorial randomized block design with the first treatment of stem cutting-derived mulberry accession being M1, M2, M3, M4, M5, M6, and M7, while the second was the concentration of NaCl at 0 mM, 40 mM, 60 mM, and 80 mM. The results showed that M2 accession from Bogor was categorized as tolerance to high salt stress, and M1 was classified as sensitive accession. Increasing salt concentration causes a decrease in growth parameters. It also decreased physiological parameters such as leaf and media relative water content while increasing dissolved sugars. Genotypic scores indicate salinity tolerance and the potential number of leaves, while Na+ content and leaf necrosis percentage showed sodium toxicity in the leaf. Therefore, genotypic score, Na+/K+ ratio, and leaf necrosis percentage are the best parameters to select and identify mulberry accession with high salt stress tolerance.